Effects of vitamin D supplementation in obese and overweight children and adolescents: A systematic review and meta-analysis - Antonio Corsello; Marina Macchi; Veronica D'Oria; Chiara Pigazzi; Ilaria Alberti; Giorgio Treglia; Valentina De Cosmi; Alessandra Mazzocchi; Carlo Agostoni; Gregorio Paolo Milani (Elsevier, 2023)
Due to the lipophilic nature of vitamin D, overweight and obese patients have an increased risk of inadequate circulating 25-hydroxy-vitamin D (25(OH)D) concentrations. Vitamin D deficiency has in turn several consequences especially among children and adolescents. Therefore, a few supplementation strategies of vitamin D for pediatric subjects with an excessive body weight have been proposed, but their efficacy remains controversial. The aim of this systematic review and meta-analysis was to evaluate the effect of vitamin D supplementation in overweight and obese children and adolescents. Three databases (PubMed, Embase and Web of Science) were searched to collect trials on the effect of vitamin D supplementation in the pediatric overweight or obese population. Twenty-three studies were included in the systematic review. Results on modification of metabolic or cardiovascular outcomes were controversial. On the other hand, the meta-analysis showed a mean difference by 1.6 ng/ml in subjects supplemented with vitamin D as compared to placebo. In conclusion, vitamin D supplementation slightly increases 25(OH)D levels in pediatric subjects with overweight and obesity. However, the effects on metabolic and cardiovascular outcomes remain controversial. New efforts should be devoted to promoting effective interventions to improve the health of children and adolescents with overweight and obesity.